Cork wastes treatment and biogas production - Gil, Luís (2014)
Cork industry is an important economic and social sector in the western Mediterranean region. Portugal is the producer and processing leader of this sector. The cork processing industry gives rise to several effluents that must be treated and valorised. This work is a part of a study that aims to develop an integrated process in order to maximize the valorization of the different wastes/effluents of the cork processing sector taking in count the biorefinery concept. The main objective of the present work is to conduct a survey of all operations involve in the cork processing and identify the possible effluents which may be treated and valorise by anaerobic digestion for energy production.